UTILIZATION OF LANDSAT 7 AND 8 IMAGES FOR MAPPING OF CHANGES IN THE NORTH COAST MANGROVE AREA, AESESA DISTRICT - Wea, Maria Matilda; Rahmawati, Arfita; Hasan, Muhammad Husain (Universitas Sebelas Maret (UNS), 2023)
In 2019 there was damage to the mangrove forest which was converted into fish ponds by cutting down 200 hectares of mangrove land in Aeramo Village, which is the northern coastal area of Aesesa District, Nagekeo Regency. This study aims to map changes in mangrove areas and determine mangrove density values.This study uses the NDVI (Normalized Difference Vegetation Index) analysis technique to determine the density of mangrove vegetation in 2011, 2016 and 2021 using Landsat 7 and Landsat 8 imagery and uses an overlay analysis technique from the results of classifying mangrove density classes to determine changes in the area of mangrove areas. The results of the study show that the mangrove area on the north coast of Aesesa District shows density values that vary with The range of vegetation density index in Landsat 7 imagery in 2011 is from -0.573770464 to 0.54666682, in 2016 it has a vegetation density index range from -0.291984737 to 0.609456897 and in 2021 it has a vegetation density index range from -0.067266561 to 0.579148531 which is divided into 5 density classes namely; very rare, rare, moderate, rare and very tight. Based on the classification results, the results of changes in the mangrove area decreased to the medium class with forest area from 102.35 hectares to 66.86 hectares from 2011 to 2016 and experienced the largest increase in the very dense class in 2011-2016 where the forest area was in the very dense class. meeting from 128.86 hectares to 210.65 hectares.